Patient Outcomes and Hospital Nurses' Workload: A Cross-Sectional Observational Study in Slovenian Hospitals Using the RN4CAST Survey - SKELA-SAVIČ Brigita; ALBREHT Tit; SERMEUS Walter; LOBE Bojana; BAHUN Mateja; DELLO Simon (Sciendo, 2023)
Higher nursing workload increases the odds of patient deaths, as the work environment has a significant effect on patient outcomes. The aim of the study was to explore the relation between patient outcomes and nurses' working conditions in hospitals.